HEALTH SHOCKS AND LABOR SUPPLY RESPONSES: EVIDENCE FROM URBAN NORTH-CENTRAL OF NIGERIA - Ogebe, O. F.; Weye, A. E.; Nnama, U. C. (Journal of Agripreneurship and Sustainable Development, 2020)
The study was conducted in three (3) States of the North-Central Nigeria to investigate households’ labor supply to health shocks in urban north-central of Nigeria. A multi-stage sampling technique was employed to select 900 households from 18 Council Wards across the three (3) States of north-central of Nigeria covering a period of five (5) months (March to July, 2019). The study found that labor supply was an important response to illness as households increased their labor supply in response to illness shocks. The results showed that 14% of men and 21% of women employed in the study areas missed at least one day of work due to unanticipated illness. Also, women in the labor force missed work due to illness or caregiving duties in 6.2% of weeks and 3.2% of weeks for men. Men and women work more in order to increase their take-home pay and compensate for the lost income due to absence from work of another household members. The findings further showed that men were 7.8% points more likely to work in weeks in which another worker in the household is unexpectedly ill. The men worked an average of 0.385 more days (P = 0.13) and 4.9 more hours as the result of the illness of a fellow worker in the household. It was also disclosed that the overall labor supply response (P = 0.17) was driven by males in households with less assets and education. The regression estimates showed that males in wealthier households were less likely to increase labor supply when another worker in the household was unexpectedly ill. A one (1) standard deviation increase in assets was associated with 0.313 fewer days worked by man in response to an illness shock (P = 0.17) and fewer hours (P = 0.15) implying that wealthier households had fungible savings that they can access to smoothen consumption after short-run shocks. The study also found that total household earnings fell by N91.00 and N72.00 when men and women, respectively, missed work because of illness. The estimated labor hour’s responses showed a larger drop of 32 hours for male illness and 18 hours for female. It was concluded that despite the increase in labor supply from other males in the household, total household income and labor supply decreased when a household member was unexpectedly ill. The study recommended health insurance policies by the government towards a reduction of illness burden for the households in the study area.